Maternal Late-Pregnancy Serum Unmetabolized Folic Acid Concentrations Are Not Associated with Infant Allergic Disease: A Prospective Cohort Study. Issue 6 (13th April 2021) - Best, Karen P; Green, Tim J; Sulistyoningrum, Dian C; Sullivan, Thomas R; Aufreiter, Susanne; Prescott, Susan L; Makrides, Maria; Skubisz, Monika; O'Connor, Deborah L; Palmer, Debra J
ABSTRACT: Background: The increase in childhood allergic disease in recent decades has coincided with increased folic acid intakes during pregnancy. Circulating unmetabolized folic acid (UMFA) has been proposed as a biomarker of excessive folic acid intake. Objective: We aimed to determine if late-pregnancy serum UMFA and total folate concentrations were associated with allergic disease risk in the offspring at 1 y of age in a population at high risk of allergy. Methods: The cohort consisted of 561 mother–infant pairs from Western Australia. To be eligible the infant had to have a first-degree relative (mother, father, or sibling) with a history of medically diagnosed allergic disease. Maternal venous blood was collected between 36 and 40 wk of gestation. Serum UMFA was measured by LC–tandem MS. Serum total folate was determined using a microbiological method with chloramphenicol-resistant Lactobacillus rhamnosus as the test organism, and was collected between 36 and 40 wk of gestation. UMFA concentrations were measured by tandem MS using stable isotope dilution; folate concentrations were determined using the microbiological method with standardized kits. Infant allergic disease outcomes of medically diagnosed eczema, steroid-treated eczema, atopic eczema, IgE-mediated food allergy, allergen sensitization, and medically diagnosed wheeze were assessed at 1 y of age. Results: Median (IQR) concentrations for UMFA and serum folate were 1.6 (0.6–4.7) and 53.2 (32.6–74.5) nmol/L, respectively. Of the infants, 34.6% had medically diagnosed eczema, 26.4% allergen sensitization, and 14.9% had an IgE-mediated food allergy. In both adjusted and unadjusted models there was little evidence of association between UMFA or serum folate and any of the infant allergy outcomes. Conclusions: In this cohort of children at high risk of allergic disease there was no association between maternal UMFA or serum folate concentrations measured in late pregnancy and allergic disease outcomes at 1 y of age.